Mosques and Imams: Everyday Islam in Eastern Indonesia - Rachma, Alviani (Universitas Islam Internasional Indonesia, 2022)
This compilation features nine excellent contributions from authors who studied the role of local imams and mosques in eastern Indonesia as part of the project “Being Muslim in Eastern Indonesia: Practice, Politics, and Cultural Diversity” funded by Australian Research Council Discovery Project. The research examines not only the role of imams in eastern Indonesia, but also discusses the process and sociocultural impacts of Islam on Islamic identity and religious authority in the region. Moreover, it also examines how Islam is practiced at the local level and the way in which village imams wield religious authority. By appreciating Indonesia’s cultural wealth and respecting the variety of Islamic traditions in Indonesia, this book provides insights into the development of Islam and its relationship with local traditions, which accommodate local communities, globalisation, culture and Islam.